Design of GaAsNBi/GaAs quantum well laser with emission wavelength of 1.55um - Chen, Ruiming (2017)
GaAs-based laser diode with emission wavelength of 1.55um are highly demand due to their potential applications in optical fiber communication. We will use k.p method to calculate the energy level and optical transition to design a 1.55um GaAsNBi/GaAs quantum well laser diodes. The N and Bi compositions and well width will be adjusted and optimized to meet the 1.55um wavelength requirement.